High results and lower cost in four-bone arthrodesis with retrograde screws - Dariush Ghargozloo; Alessandro Tomarchio; Mauro Ballerini; Emanuela Saccalani; Giorgio Grazioli; Gianpaolo Chitoni (Medicinski glasnik, 2022)
Aim: To describe the technique of the four-corner fusion with two retrograde crossed headless screws in cases of carpal collapse. Methods: This technique is a consolidated procedure performed in cases of scaphoid non- union advanced collapse (SNAC) type II and III, scapholunate advanced collapse (SLAC) type II and III and in other cases of carpal collapse. Between 2017 and 2019 we treated six male patients (a mean age of 55.0 years) with radiocarpal osteoarthritis. Our technique involves the use of two retrograde crossed headless screws; the first screw was placed distally proximally from the uncinate to the lunate and the second screw from the pyramidal to the capitate, crossed at approximately 90 degrees. Clinical and radiographic two-year follow-up was performed. Before the treatment and during the follow-ups VAS, PRWE and DASH Quick score scales, measured wrist range of motion (WROM) were administered and evaluated. Results: In all cases the X-ray consolidation of arthrodesis within five months was noticed; in 50% patients already under 3-month control. No observed signs of mobilization of screws and inflammatory or infectious processes were found. All patients were satisfied (reduction/disappearance of pain). All surgically treated patients resumed normal daily activities. These improvements were confirmed by the results of the evaluation scale and clinical examination. Conclusion: This technique, in our opinion, represents a gold standard. Its low costs of the material used (especially comparing to other technique), a low prevalence of complications of materials and fusion in 100% of cases should be also considered.
Keywords: compressive screw; four-corner fusion; SLAC wrist; SNAC wrist